Perbedaan Kadar Hemoglobin Pada Sampel Darah yang Dihomogenisasi Sekunder Inversi 2 Kali dan 8 Kali Setelah Ditunda Selama 30 Menit dengan Hematology Analyzer - Miftahul Jannah; Rosnita Sebayang; Mustika Sari Hutabarat (Fakultas ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Hemoglobin test is one of the tests performed in a clinical laboratory that aims to determine the hemoglobin level in a person's body. The sample used in hemoglobin examination is blood with EDTA anticoagulant. Anticoagulants act to inactivate blood clotting factors. Therefore, blood that has been put into a tube with anticoagulant must be immediately primary homogenized. In the field, blood samples that have been collected are usually not immediately examined, resulting in delays. Blood that has been primary homogenized if left to stand will experience precipitation. Therefore, blood samples must be re-homogenized (secondary homogenization) before testing. To see if there is a difference in hemoglobin levels secondary homogenized 2 and 8 times after standing for 30 minutes. This type of research is observational research with cross sectional research design. The research subjects examined were 32 people. The study subjects had their blood drawn in 2 tubes and then each tube was primary homogenized 8 times and allowed to stand for 30 minutes. After 30 minutes, the tube with code A was secondary homogenized 2 times and then examined on the Sysmex XP-100 device and the tube with code B was secondary homogenized 8 times and then examined on the Sysmex XP-100 device. Data were analyzed using Paired Sample T- Test test with 95% confidence level. Hemoglobin levels for tubes that were secondary homogenized 2 times obtained a mean value of 13.2 g/dL and standard deviation (SD) 1.17 g/dL while for tubes that were secondary homogenized 8 times obtained a mean value of 13.2 g/dL and SD 1.13 g/dL. Statistical test results showed that there was no p = 0.567 (>0.05). Based on the results of the study it can be concluded that there is no significant difference in the results of secondary homogenized tubes 2 times and 8 times. In future studies, the number of samples used should be increased again.